Abnormal Electromechanical Property of Nonlinearly Graded Lead‐Free Ferroelectric Thin Films (Adv. Theory Simul. 2/2022). Issue 2 (10th February 2022) - Lich, Le Van; Bui, Tinh Quoc; Shimada, Takahiro; Kitamura, Takayuki; Hong, Hue Dang Thi; Nguyen, Trong‐Giang; Dinh, Van‐Hai
Abstract : Large piezoelectric effect in nonlinearly graded lead‐free ferroelectric thin films In article number 2100370, using extended phase field simulations, Le Van Lich and co‐workers demonstrate that a large piezoelectric effect can be obtained in nonlinearly graded lead‐free ferroelectric thin film. The enhancement of piezoelectric property originates from the large gradient of electrical polarization, which makes the polarization field more susceptible to external excitation.